Characterization of the Impact of Density Gradient Centrifugation on the Profile of the Pig Sperm Transcriptome by RNA-Seq - Lian, Yu; Gòdia, Marta; Castello, Anna; Rodriguez-Gil, Joan Enric; Balasch, Sam; Sanchez, Armand; Clop, Alex (Frontiers in Veterinary Science, 2021)
RNA-Seq data from human semen suggests that the study of the sperm transcriptome requires the previous elimination from the ejaculates of somatic cells carrying a larger load of RNA. Semen purification is also carried to study the sperm transcriptome in other species including swine and it is often done by density gradient centrifugation to obtain viable spermatozoa from fresh ejaculates or artificial insemination doses, thereby limiting the throughput and remoteness of the samples that can be processed in one study. The aim of this work was to evaluate the impact of purification with density gradient centrifugation by BoviPureTM on porcine sperm. Four boar ejaculates were purified with BoviPureTM and their transcriptome sequenced by RNA-Seq was compared with the RNA-Seq profiles of their paired non-purified sample. 7,519 protein coding genes were identified. Correlation, cluster and principal component analysis indicated high - although not complete - similarity between the purified and the paired non-purified ejaculates. 372 genes displayed differentially abundant RNA levels between treatments. Most of these genes had lower abundances after purification and were mostly related to translation, transcription and metabolic processes. We detected a significant change in the proportion of genes of epididymal origin within the differentially abundant genes (1.3%) when compared with the catalogue of unaltered genes (0.2%). In contrast, the proportion of testis-specific genes was higher in the group of unaltered genes (4%) when compared to the list of differentially abundant genes (0%). No proportion differences were identified for prostate, white blood, lymph node, tonsil, duodenum, skeletal muscle, liver and mammary gland. Altogether, these results suggest that the purification impacts on the RNA levels of a small number of genes which are most likely caused by the removal of epididymal epithelial cells but also premature germinal cells, immature or abnormal spermatozoa or seminal exosomes with a distinct load of RNAs.